Disentangling the Effects of a Banking Crisis: Evidence from German Firms and Counties - Huber, Kilian (American Economic Review, 2018)
Lending cuts by banks directly affect the firms borrowing from them, but also indirectly depress economic activity in the regions in which they operate. This paper moves beyond firm-level studies by estimating the effects of an exogenous lending cut by a large German bank on firms and counties. I construct an instrument for regional exposure to the lending cut based on a historic, postwar breakup of the bank. I present evidence that the lending cut affected firms independently of their banking relationships, through lower aggregate demand and agglomeration spillovers in counties exposed to the lending cut. Output and employment remained persistently low even after bank lending had normalized. Innovation and productivity fell, consistent with the persistent effects. (JEL E32, E44, G01, G21, G32, R11, R23)